The development of flashcard learning media based on make a match on colloid - Fitriani, Henni; Imanda, Riska; Rahmi, Ayu; Nurmalinda, Siti (International Journal for Educational and Vocational Studies, 2021)
This study aimed to determined the feasibility of the Make a Match-Based Flashcard learning media on colloidal material. The subjects of this study were the students of the State Senior High School 1 Muara Batu and the Private High School Jabalnur as many as 25 students. This study refers to the type of Research and Development (R&D) with a 4D model. This research was carried out until the limited trial stage. The stages carried out in this research are Define, Design, Develop. In the Define stage, concept analysis is carried out, at the design stage, the design of learning media to be developed is carried out, at the Develop stage the development of Make a Match-Based Flashcard media is carried out and limited trials on research subjects. The results showed that the Make a Match-Based Flashcard media was valid with a media validity percentage of 88% (very good), and material validity of 85% (very good). The results of data analysis showed the feasibility with a percentage value of 92.30% (very feasible). Based on the results of the study conducted, it can be concluded that the Make a Match-Based Flashcard media is very suitable to be used as a learning medium on colloidal material.